Financial and cost accounting for management : the fundamentals of modern accounting techniques - Taylor, Anthony Herbert; Shearing, H. (London : Macdonald and Evans, 1974)
This new edition has been brought up to date in respect of changes in the business environment, accounting practice and the law relating to accounting. A new chapter on computerization has been added. Mergers, replacement costs and inflation, and capital budgeting are among several topics that have been expanded.
Includes bibliographical references and index.
hza 11/09/2018
Loans
Keywords: Accounting